Differential distribution of endoplasmic reticulum controls metabotropic signaling and plasticity at hippocampal synapses - Holbro, Niklaus (National Academy of Sciences, 2009)
Synaptic plasticity is considered essential for learning and storage of new memories. Whether all synapses on a given neuron have the same ability to express long-term plasticity is not well understood. Synaptic microanatomy could affect the function of local signaling cascades and thus differentially regulate the potential for plasticity at individual synapses. Here, we investigate how the presence of endoplasmic reticulum (ER) in dendritic spines of CA1 pyramidal neurons affects postsynaptic signaling. We show that the ER is targeted selectively to large spines containing strong synapses. In ER-containing spines, we frequently observed synaptically triggered calcium release events of very large amplitudes. Low-frequency stimulation of these spines induced a permanent depression of synaptic potency that was independent of NMDA receptor activation and specific to the stimulated synapses. In contrast, no functional changes were induced in the majority of spines lacking ER. Both calcium release events and long-term depression depended on the activation of metabotropic glutamate receptors and inositol trisphosphate receptors. In summary, spine microanatomy is a reliable indicator for the presence of specific signaling cascades that govern plasticity on a micrometer scale.